Update on Heart Failure Treatment and Outcomes in the Caribbean - Jacobson, Anne (MD Conference Express, 2010)
Heart failure is an emerging threat in the Caribbean Islands; yet, with no data on heart failure risks and outcomes in the Caribbean population, physicians are not fully prepared to address this problem. To fill this important information gap, the Caribbean Cardiac Society (CCS) has launched the CCS Survey on Heart Failure.